A Sosialisasi Pemadaman Kebakaran Dilingkungan Rumah - Liswandi; Hanafiah, Hally; Rahadi, Dedi Rianto (Lentera Ilmu Madani, 2024)
In the home environment, fires can occur due to the use or carelessness in using electrical equipment, gas stoves, burning garbage, and cigarette butts. Often, people do not know how to handle fires. We teach people how to handle fires at home. The purpose of this activity is to provide basic knowledge and understanding of how to extinguish fires in the home environment using equipment commonly used to extinguish fires. In addition, people are informed about the factors that cause fires and how to handle them without causing panic. The results of the training showed that some people do not yet understand the factors that cause fires and how to handle them without causing panic. The community has been trained and educated about what causes fires and how to deal with them if a fire occurs. The community is trained to extinguish fires using wet sacks and fire extinguishers.